Age-dependent structural reorganization of utricular ribbon synapses - Michanski, Susann; Henneck, Timo; Mukhopadhyay, Mohona; Steyer, Anna M.; Gonzalez, Paola Agüi; Grewe, Katharina; Ilgen, Peter; Gültas, Mehmet; Fornasiero, Eugenio F.; Jakobs, Stefan; Möbius, Wiebke; Vogl, Christian; et al. (Frontiers in Cell and Developmental Biology, 2023)
In mammals, spatial orientation is synaptically-encoded by sensory hair cells of the vestibular labyrinth. Vestibular hair cells (VHCs) harbor synaptic ribbons at their presynaptic active zones (AZs), which play a critical role in molecular scaffolding and facilitate synaptic release and vesicular replenishment. With advancing age, the prevalence of vestibular deficits increases; yet, the underlying mechanisms are not well understood and the possible accompanying morphological changes in the VHC synapses have not yet been systematically examined. We investigated the effects of maturation and aging on the ultrastructure of the ribbon-type AZs in murine utricles using various electron microscopic techniques and combined them with confocal and super-resolution light microscopy as well as metabolic imaging up to one year of age.In older animals, we detected predominantly in type I VHCs the formation of floating ribbon clusters. Our findings suggest that VHC ribbon-type AZs undergo dramatic structural alterations upon aging.